2011
DOI: 10.1166/jnn.2011.4803
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of Polymer Nanocomposite Resists Containing Metal Nanoparticles by Electron Beam Lithography

Abstract: Poly(vinyl pyrrolidone) (PVP)-stabilized silver nanoparticles (NPs) were used as a new nanocomposite resist for electron beam lithography. A nanocomposite resist prepared by reducing silver nitrate in an alcoholic PVP solution was patterned by using a scanning electron microscope equipped with a nanometer pattern generation system. Well-defined negative tone patterns with a good sensitivity of 200 microC/cm2 and a contrast of 2.83 were obtained using the prepared nanocomposite resist. In addition, the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…PVP used as a stabilizer for Ag NPs have been reported by Lee et al in patterning of a nanocomposite resist for electron beam lithography [200] . It is also used in synthesis of Ag NPs by gamma, electron beam, and synchrotron X-ray irradiation [201] .…”
Section: Lithography and Photographymentioning
confidence: 99%
“…PVP used as a stabilizer for Ag NPs have been reported by Lee et al in patterning of a nanocomposite resist for electron beam lithography [200] . It is also used in synthesis of Ag NPs by gamma, electron beam, and synchrotron X-ray irradiation [201] .…”
Section: Lithography and Photographymentioning
confidence: 99%
“…Much less is known about how electrons interact with the water‐soluble polymer precursors often used in biorelevant patterning applications such as poly(ethylene glycol) [PEG], poly(vinyl pyrrolidone) [PVP], poly (acrylic acid) [PAA], or polyacrylimide . PEG films, for example, can be e‐beam processed to create surface‐patterned hydrogels that resist nonspecific protein adsorption and cell adhesion .…”
Section: Introductionmentioning
confidence: 99%
“…Further reports demonstrate that if Ag or Au salts are added to polyvinyl alcohol, electron beam exposure can induce acid catalyzed crosslinking within polyvinyl alcohol rendering the exposed regions insoluble in water thus exhibiting negative-tone behavior 159 , 160 . The addition of silver nitrate to poly(vinyl pyrrolidone) also exhibited negative-tone pattern ability; however, it was found that the nanocomposite formulation showed lower patterning resolution 161 . Better results were obtained for a negative resist that consists of chloroauric acid (HAuCl4) and poly(vinyl pyrrolidone) hybrid, giving a minimum Au feature size of 100 nm after electron beam lithography 162 …”
Section: Metal-containing Resists In Electron Beam Lithography: An Ov...mentioning
confidence: 99%
“…159,160 The addition of silver nitrate to poly(vinyl pyrrolidone) also exhibited negative-tone pattern ability; however, it was found that the nanocomposite formulation showed lower patterning resolution. 161 Better results were obtained for a negative resist that consists of chloroauric acid (HAuCl 4 ) and poly(vinyl pyrrolidone) hybrid, giving a minimum Au feature size of ∼100 nm after electron beam lithography. 162 In a recent report, the addition of ∼2-nm-sized Ag nanoparticles to tert-butyl 2-ethyl-6-(4hydroxyphenyl)-4-phenylheptanoate (Terpolymer) resist served as radiation sensitizer.…”
Section: Metal-containing Polymeric Resistsmentioning
confidence: 99%